PERBANDINGAN BESAR GAYA ROTATING SPRING BUATAN PABRIK DAN TANGAN PADA TEKNIK BEGG - , Trio Wijayanto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Correction of tooth rotation is one the first steps in Beggâs orthodontic technique, friction between archwire and bracket occurs when rotated tooth is being corrected, rotating spring is used to correct the rotated teeth. The purpose of this study was to determine: a. the difference of the amount of rotating force between hand made and fabricated rotating springs, counter-clockwise and clockwise rotating springs, which diameter are 0.012, 0.014, and 0.016 inch. b. interaction between factors which are hand made and fabricated (in the way theyare made) and the direction of the rotating spring whether they are clockwise or counter-clockwise